Improving Long Jump Learning Outcomes Through the Discovery Learning Approach in Class XI Students of SMA Negeri 1 Rantau Selamat - Zulkifli (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
The general objective of this research is to improve student outcomes through the application of Volleyball Learning using Problem-Based Learning (PBL). Additionally, this research is conducted to gain in-depth information about the implementation of the Underhand Passing Learning using PBL. The research design is Action Research. The subjects in this study are 22 students from the Eighth grade at SMPN 4 Birem Bayeun. This research was conducted over two meetings consisting of two cycles. Each cycle consists of three sessions. The first cycle shows that through actions, students can self-motivate. From this first cycle, the result is 43%, indicating it is not yet complete. In the second cycle, as a reflection of the first cycle, it also shows that actions improve student learning outcomes. The result of the second cycle is 87%, indicating completion. Based on the results of this research, it can be concluded that: (1) Volleyball Learning using PBL enhances student learning outcomes, (2) Underhand Passing Learning using PBL motivates students and makes them active participants in the learning process.